The effect of using PhET simulation media on energy and work materials on improving students' learning outcomes and critical thinking skills: A literature study - Fajar Purwono; Ade Suhendar; Saeful Fathani; Fauzul Fadli; Rina Hidayati Pratiwi (Privietlab, 2025)
Physics education depends on work and energy concepts because they enable students to understand the natural events and technological systems. Students face challenges when learning these concepts because they exist at an abstract level and require a complex understanding while facing restrictions from limited resources and traditional teaching approaches. Students who study energy and work face poor learning results because they lack motivation and critical-thinking abilities. Research from 15 recent academic journals shows that digital education advancements have led to the development of multiple interactive learning tools, including the Physics Education Technology (PhET) Simulation. The implementation of Physics Education Technology (PhET) simulation media has demonstrated successful solutions to overcome learning challenges. The interactive visualizations in PhET media enable students to explore concepts independently, which leads to a better understanding of subjects, improved cognitive, affective, and psychomotor learning results, enhanced critical thinking abilities, and improved scientific literacy. The combination of PhET media with innovative learning approaches, including guided inquiry, problem-based learning, and blended learning, enhances student learning effectiveness for energy and work subjects. The PhET simulation platform functions as an optimal educational resource that enhances physics education quality, specifically for energy and work subjects, to help students reach their best learning potential and develop critical thinking abilities at different educational levels.